Fe2O3@SiTi core–shell catalyst for the selective catalytic reduction of NOx with NH3: activity improvement and HCl tolerance. Issue 13 (13th June 2018) - Chang, Huazhen; Zhang, Tao; Dang, Hao; Chen, Xiaoyin; You, Yanchen; Schwank, Johannes W.; Li, Junhua
Abstract : A core–shell structured Fe2 O3 @SiTi catalyst with a SiTi shell and Fe2 O3 core was prepared and used for the selective catalytic reduction (SCR) of NO x with NH3 . Abstract : A core–shell structured Fe2 O3 @SiTi catalyst with a SiTi shell and Fe2 O3 core was prepared and used for the selective catalytic reduction (SCR) of NO x with NH3 . The thickness of the shell could be well controlled by the amount of TEOS added during the preparation procedure. The catalyst was characterized by techniques including STEM, XRD, BET, NH3 -TPD, XPS, and H2 -TPR. In comparison with Fe2 O3, the Fe2 O3 @SiTi catalyst presented higher SCR activity, N2 selectivity, better SO2 resistance and HCl tolerance. The characterization results showed that the addition of the SiTi shell onto the Fe2 O3 core enlarged the BET specific surface area, increased the number of surface acidic sites, led to the generation of more Fe 2+ species and chemisorbed oxygen species, and influenced the reducibility of Fe2 O3 . The improvement of HCl tolerance of the Fe2 O3 @SiTi catalyst can be attributed to the fact that the SiTi shell prevents the Fe2 O3 core from reacting with HCl to form FeCl3 .